Improvement of the Early, Middle and Final Patrol Check Process From Manual to Digital with the PDCA Method, Fishbone Diagram, and Why-Why Analysis at PT. Automotive Components Company - Chairul Alfatory; Bintang Rafly Aryansyah; Mahendra Mahendra; Andhika Danisvara; Yudi Prastyo (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
The Checksheet process at PT. Automotive component companies are an important activity to maintain quality consistency in the production of automotive components, especially brackets. However, the inspection method that is still carried out manually causes waste of time, high use of paper, and increased operational costs. This study aims to reduce the cycle time of Patrol Check A-T-A, implement a digital (paperless) recording system, and improve process efficiency through the PDCA (Plan-Do-Check-Act) approach, Fishbone Diagram, and Why-Why Analysis. The results of the identification of the root of the problem show that the absence of a standardized digital system and the lack of management initiatives are the main causes of the long inspection process and high paper consumption. The implementation of E-Checksheet as a digital solution resulted in a significant reduction in cycle time, from 50 minutes to 10 minutes, as well as eliminating paper use by up to 100%. In addition, workflows become simpler, data is easier to monitor, and processes become more efficient. This study concludes that the digitization of Checksheet is able to increase operational effectiveness, reduce waste, and support continuous improvement in the manufacturing environment.